2020
DOI: 10.3389/fpls.2020.01174
|View full text |Cite
|
Sign up to set email alerts
|

NDVI Changes Show Warming Increases the Length of the Green Season at Tundra Communities in Northern Alaska: A Fine-Scale Analysis

Abstract: dependent on community composition and abundance of specific growth forms and therefore will likely impact net primary productivity and trophic interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 80 publications
1
15
0
Order By: Relevance
“…Our results suggest that because more GDD contribute to an earlier start and end to the growing season in every vegetation community, warmer conditions are unlikely to extend the growing season in these communities. This finding corroborates Arctic plot‐scale field studies indicating warming does not lengthen the growing season but can shift it earlier (Starr et al, 2000; Khorsand Rosa et al, 2015 but see May et al, 2020), and complements remote sensing observations that show no or little trend of lengthening growing season in much of the Arctic (Gamon et al, 2013; Gonsamo et al, 2018; Zhao et al, 2015). The absence of a change in growing season length for Arctic plants in response to warming is likely due to the accumulation of water deficit due greater evapotranspiration during the warmer spring, a phenomenon which has been recently observed in many ecosystems, including those typically thought to be temperature‐limited (Angert et al, 2005; Buermann et al, 2018; Gonsamo et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…Our results suggest that because more GDD contribute to an earlier start and end to the growing season in every vegetation community, warmer conditions are unlikely to extend the growing season in these communities. This finding corroborates Arctic plot‐scale field studies indicating warming does not lengthen the growing season but can shift it earlier (Starr et al, 2000; Khorsand Rosa et al, 2015 but see May et al, 2020), and complements remote sensing observations that show no or little trend of lengthening growing season in much of the Arctic (Gamon et al, 2013; Gonsamo et al, 2018; Zhao et al, 2015). The absence of a change in growing season length for Arctic plants in response to warming is likely due to the accumulation of water deficit due greater evapotranspiration during the warmer spring, a phenomenon which has been recently observed in many ecosystems, including those typically thought to be temperature‐limited (Angert et al, 2005; Buermann et al, 2018; Gonsamo et al, 2019).…”
Section: Discussionsupporting
confidence: 82%
“…Our study showed that tussocks across all populations stayed green for 3.76 days longer in response to direct warming but little else was responsive, therefore it is not clear whether the response of E. vaginatum to a gradual temperature increase will have tangible ecosystem effects. OTC experiments have recently shown that tundra plant communities (including moist acidic tundra, dominated by E. vaginatum) extend their growing season when warmed (May et al 2020). This suggests that contemporary plant communities can take advantage of milder growing conditions, at least in the short term.…”
Section: Effects Of Transplanting On Phenology Of Eriophorum Vaginatummentioning
confidence: 99%
“…At the beginning of the growing season, earlier snowmelt should result in earlier green-up, as abundant sunshine and the disappearance of snow produces good growing conditions. Many studies have documented the importance of snowmelt timing for controlling the phenology of arctic plants with earlier snowmelt, which usually results in earlier onset of growth (Høye et al 2007;Bjorkman et al 2015;Khorsand Rosa et al 2015;Semenchuk et al 2016;May et al 2020). Once the growing season is underway, it is less clear whether higher average temperatures will affect plant phenology in part because of interactions with snowmelt timing (Oberbauer et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for each grassland grid, the slope value of NDVI (NDVIs) from 2005 to 2018 could be used to indicate the trend of grassland change, and NDVIs values less than 0 could be regarded as grassland degradation. However, it is worth noting that NDVIs values lower than 0 do not indicate grassland degradation, because shrubencroached grasslands in alpine regions are an important form of grassland degradation and do not necessarily lead to a reduction in NDVI (Fraser et al, 2014;May et al, 2020). Therefore, to more comprehensively identify the pattern of grassland degradation, we defined grassland degradation as non-encroached degraded Taking into account the non-stationarity of ecological processes, the diversity and incompleteness of data, and the complex relationships among factors, we selected 18 potential factors based on previous research results (Kane et al, 2017;Chen et al, 2020).…”
Section: Establish the Grassland Degradation Risk Inference Modelmentioning
confidence: 99%